2018
DOI: 10.1002/jcp.27522
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin and iron regulatory proteins coordinately regulate ferroportin 1 expression in the brain of mice

Abstract: Iron plays an essential role in various cellular metabolic processes of the body.Maintenance of cellular iron homeostasis is particularly important for keeping the normal functions of the cells. Ferroportin 1 (FPN1) is the currently only known iron exporter on the cell membrane. It has been indicated that the regulation of FPN1 in response to the alteration of iron level mainly involves two processes, posttranscriptional repression by iron regulatory proteins (IRPs) and posttranslational degradation by hepcidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…At present, information on the mechanisms involved in iron transport and homeostasis in oligodendrocytes and microglia remains very limited as compared to neurons and astrocytes. In addition, how the expression of iron transport proteins is controlled in the brain under physiological conditions, and the genetic and non‐genetic causes that might lead to misregulation of brain iron metabolism are two key questions that have yet to be answered. A number of studies have provided evidence for the existence of hepcidin in the brain (Wang et al ., ; Wang et al, ; Raha‐Chowdhury et al, ; Pellegrino et al, ; Lu et al, ; Puy et al, ; Vela, ; Wang et al, ). Recent studies have shown that this iron regulatory hormone is also a central player in brain iron homeostasis and has a key role in controlling iron transport in the BBB, and iron uptake and release in astrocytes and neuronal cells (Du et al, , ; Gong et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, information on the mechanisms involved in iron transport and homeostasis in oligodendrocytes and microglia remains very limited as compared to neurons and astrocytes. In addition, how the expression of iron transport proteins is controlled in the brain under physiological conditions, and the genetic and non‐genetic causes that might lead to misregulation of brain iron metabolism are two key questions that have yet to be answered. A number of studies have provided evidence for the existence of hepcidin in the brain (Wang et al ., ; Wang et al, ; Raha‐Chowdhury et al, ; Pellegrino et al, ; Lu et al, ; Puy et al, ; Vela, ; Wang et al, ). Recent studies have shown that this iron regulatory hormone is also a central player in brain iron homeostasis and has a key role in controlling iron transport in the BBB, and iron uptake and release in astrocytes and neuronal cells (Du et al, , ; Gong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(6) A number of studies have provided evidence for the existence of hepcidin in the brain (Wang et al, 2008a;Wang et al, 2010;Raha-Chowdhury et al, 2015;Pellegrino et al, 2016;Lu et al, 2017;Puy et al, 2018;Vela, 2018;Wang et al, 2019). Recent studies have shown that this iron regulatory hormone is also a central player in brain iron homeostasis and has a key role in controlling iron transport in the BBB, and iron uptake and release in astrocytes and neuronal cells (Du et al, 2011Gong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by modulating the expression of ferroportin (Fpn), the only known iron export protein. Increased iron saturation of serum transferrin upregulates the secretion of liver hepcidin, which binds Fpn on the plasma membrane of cells and causes its internalization and degradation [ 106 ]. This decreases both iron uptake from the intestine and release from iron stores, reducing the circulating iron.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the endoplasmic reticulum stress‐related factor CCAAT/C/EBP homologous protein (CHOP) has been found to promote hepcidin expression by regulating C/EBPα activity in male SD rats with subarachnoid hemorrhage, indicating that the CHOP pathway is one of the routes for control of hepcidin expression in the brain . In addition, the regulation of hepcidin on Fpn1 expression was found to be coordinated with iron regulatory proteins …”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 99%